2009
DOI: 10.1016/j.jacc.2008.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Fibrosis Applying Contrast-Enhanced Cardiac Magnetic Resonance in Different Forms of Left Ventricular Hypertrophy

Abstract: Fibrosis as detected by CMR is a frequent feature of LVH, regardless of its cause, and depends on the severity of LV remodeling. As LGE emerges as a useful tool for risk stratification also in nonischemic heart diseases, our findings have the potential to individualize treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
189
1
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 325 publications
(225 citation statements)
references
References 57 publications
16
189
1
19
Order By: Relevance
“…This, alongside the reduction in left atrial size seen in men but not women, may reflect a greater improvement in left ventricular cavity pressure, trans-mitral gradient and mitral valve tethering forces in men. 25,29 , however, these studies used different methods of MF quantification which most likely accounts for the increased values reported, rather than a true difference in absolute levels of MF.…”
Section: Discussionmentioning
confidence: 97%
“…This, alongside the reduction in left atrial size seen in men but not women, may reflect a greater improvement in left ventricular cavity pressure, trans-mitral gradient and mitral valve tethering forces in men. 25,29 , however, these studies used different methods of MF quantification which most likely accounts for the increased values reported, rather than a true difference in absolute levels of MF.…”
Section: Discussionmentioning
confidence: 97%
“…47,77, 78 Approximately 70% of HCM patients have evidence of LGE on CMR. 79, 80 Olivotto et al found substantial amounts of LGE in a subset of patients with HCM and low-normal EF values (50-65%) in comparison with patients with higher EF, 81 but little or no association was found between EF and several standard clinical and demographic parameters, such as age, sex, LV cavity dimensions, wall thickness or LVM. Myocardial fibrosis was an independent predictor of adverse outcome in the study by O'Hanlon et al, which assessed the presence, amount and prognostic role of LGE in 217 patients with HCM followed for 3.1±1.7 years.…”
Section: Myocardial Fibrosis In Primary Lvhmentioning
confidence: 98%
“…Ischemic areas are known to be localized in the subendocardial area and definitely conform to one of the particular coronary territories. Previous studies reported that the extent of nonviable tissue in a myocardial segment can be used to predict recovery of function after revascularization (28). It is generally unlikely that myocardial scar or fibrosis in which more than 50% of myocardial wall thickness is involved at cardiac MR imaging will resume contractile function in the wake of coronary revascularization (2).…”
Section: Discussionmentioning
confidence: 99%